THE MUSIC OF FULFILLED LOVES IN THE BAROQUE AND CLASSICAL ART - MĂNIUŢ, Petruţa-Maria (Studia Universitatis Babes-Bolyai Musica, 2009)
Art has scarcely recorded testimonies of fulfilled loves: either because they rarely exist, either because - whenever they do exist - they do not primary generate artistic outputs: happiness is self-sufficient and whoever lives it knows that it does not need any plus. "Only in love one can find the transcendence where two people meet surpassing actually their selves, the place where occurs a re-location of the selfish and mean ego of one's self". "If you can not transform love in that absolute in front of which any other story desists from making sense, than one should not venture on its path": this is the risk encountered by a feeling, which reaches the most touching intensity. Music masterpieces, which dare to praise love, represent this suspension of mystery, which increased especially in the Romantic repertoire.